Structure of a eukaryotic cytoplasmic pre‐40S ribosomal subunit - Scaiola, Alain; Peña, Cohue; Weisser, Melanie; Böhringer, Daniel; Leibundgut, Marc; Klingauf‐Nerurkar, Purnima; Gerhardy, Stefan; Panse, Vikram Govind; Ban, Nenad (The EMBO journal, 2018)
Final maturation of eukaryotic ribosomes occurs in the cytoplasm and requires the sequential removal of associated assembly factors and processing of the immature 20S pre‐RNA. Using cryo‐electron microscopy (cryo‐EM), we have determined the structure of a yeast cytoplasmic pre‐40S particle in complex with Enp1, Ltv1, Rio2, Tsr1, and Pno1 assembly factors poised to initiate final maturation. The structure reveals that the pre‐rRNA adopts a highly distorted conformation of its 3′ major and 3′ minor domains stabilized by the binding of the assembly factors. This observation is consistent with a mechanism that involves concerted release of the assembly factors orchestrated by the folding of the rRNA in the head of the pre‐40S subunit during the final stages of maturation. Our results provide a structural framework for the coordination of the final maturation events that drive a pre‐40S particle toward the mature form capable of engaging in translation. Synopsis A high‐resolution cryo‐EM structure of the cytoplasmic pre‐40S ribosomal subunit from yeast describes interactions between assembly factors and the immature 20S rRNA and reveals how the assembly factors check the integrity of important pre‐40S regions and prevent premature binding of mRNAs and tRNAs. A cryo‐EM structure of the pre‐40S ribosomal subunit in complex with assembly factors Enp1, Ltv1, Rio2, Tsr1 and Pno1 is determined at 3.4 Å resolution. The cytoplasmic pre‐40S subunit shows a strong distortion of the 3′ major and 3′ minor domains of the rRNA, held in place by assembly factors. Enp1 and Tsr1 interact with the beak of the pre‐40S ribosomal subunit and stabilise the tilted conformation of the small subunit head. Rio2 and Tsr1 prevent rRNA helix 44 from docking into its mature conformation, which propagates structural changes to the binding site of Pno1. Assembly factors may be released in groups of two, coupled to changes seen in the rRNA structure as the 40S subunit shifts towards the mature conformational state. Graphical Abstract A high‐resolution cryo‐EM structure of the yeast ribosome's immature 40S subunit shows how assembly factors interact with the 20S rRNA, check the integrity of important regions, and prevent premature binding of mRNAs and tRNAs.